The Effects of HIV/AIDS Worldwide - Ajit Pal Singh; Nyamojwok Charles Onak Kimo (International Journal of Virus Studies, 2024)
The Human Immunodeficiency Virus (HIV), which targets immune system conductors (CD4 cells), has infected millions throughout the world. HIV lowers the body's defences by infecting certain bodily fluids (blood, sperm, vaginal fluids, and breast milk) through unprotected sex, contaminated needles, or mother-to-child transmission. Early flu-like symptoms may go unrecognised, but if not treated, HIV advances to AIDS, which is characterised by severe immune system impairment. However, advances in antiretroviral therapy (ART) enable HIV patients to live longer lives, and PrEP medicine greatly reduces infection risk. The future of HIV prevention depends in improved education, testing, and research for vaccines and cures, as well as removing the stigma associated with the virus. Only through a concerted effort can we establish a world in which HIV infection rates fall and the virus is no longer a worldwide danger. Furthermore, tackling socioeconomic determinants of health such as poverty, gender imbalance, and stigma is critical for lowering HIV incidence and increasing the quality of life for those living with HIV.A multimodal approach is required to address the pandemic's complex interaction of biological, social, and structural variables. This strategy should include biological treatments, behavioural interventions, and efforts to address underlying health determinants. HIV predominantly targets CD4 cells, which weakens the immune system.
Keywords: Antiretroviral Therapy (ART); HIV/AIDS; Immune system; Prevention and PrEP; Socioeconomic Determinants